Pengembangan Alat Permainan Edukatif (APE) Robot Jati Diri sebagai Media Pembelajaran untuk Implementasi Kurikulum Merdeka PAUD - Lina Eka Retnaningsih; Mahfuzah Saniah; Aidillah Suja; Sri Amanda; Karni; Enggel Purnama Wulandari (JCE (Journal of Childhood Education), 2025)
The Merdeka Curriculum for Early Childhood Education introduces a novel component termed the Self-Identity element; however, learning media that adequately support its associated learning outcomes remain limited. This study aimed to develop an educational play tool, the "Robot Jati Diri," as an instructional medium to facilitate the implementation of the Self-Identity element for children aged 5–6 years. Employing a Research and Development (R&D) design with the 4D model (Define, Design, Develop, Disseminate), product feasibility was validated by content and media experts. The results indicated that the product met the criteria of "highly feasible," with validation scores of 84% (media expert) and 86% (content expert). A small-group trial at TK Negeri Pembina Bintan further demonstrated positive pedagogical responsiveness, wherein 90% of children engaged autonomously and exhibited high levels of enthusiasm across all four instructional facets (self-recognition, emotional identification, gender differentiation, and family roles). The novelty of this development lies in the comprehensive operationalization of the Self-Identity element into a single four-sided physical APE, enabling simultaneous stimulation of cognitive, socio-emotional, fine motor, and language domains. The findings underscore the potential of the Self-Identity Robot as a practical pedagogy-supporting medium for Merdeka Curriculum implementation in PAUD settings and as an effective alternative for promoting meaningful play-based learning experiences aligned with Self-Identity learning outcomes.